Evaluasi Profit dan Kelayakan Finansial Budidaya Pembesaran Ikan Lele Menggunakan Pakan Pelet pada Pokdakan Mina Tanjung Makmur Kabupaten Tulungagung - Susadiana Susadiana; Mochammad Fattah; Pudji Purwanti; Dwi Sofiati; Asyifa Anandya; Diana Aisyah (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
Catfish is an edible fish which is one of the leading commodity in Indonesia. The development of catfish farming techniques is used to meet market demand. The aims of this study are to analyze the profit and feasibility of pellet feeding on catfish farming. Data analysis in this study uses R/C, BEP, revenue, rentability, NPV, B/C, IRR and PBP. Pellet feeding on catfish farming uses concrete ponds, tarpaulin and soil, while it reached 90% for the survival rate. Catfish farming with pellet feeding showed profitable and feasible as it obtained the R/C value of 1.40; BEP of IDR 37,413,242; BEPq of 691 Kg; revenue of IDR 89,505,700; rentability of 40%; NPV of IDR 225,827,167.31; B/C of 1.81; IRR of 29.6% and PBP of 3.13. Farmers can increase their profit through developing the most efficient fish farming techniques for their own to produce the catfish.